Qualitative analysis of Indonesian hospital pharmacist’s perceptions of their roles and behaviour during the covid-19 pandemic - Prasetyaningrum, Dina Ayu; Purwonugroho, Tunggul Adi; Mustikaningtia, Ika; Ilma, Dewi Latifatul; Sholihat, Nia Kurnia; Maharani, Laksmi (Rumah Sakit Akademik Universitas Gadjah Mada, 2024)
AbstractBackground: Pharmacists are health workers who play an important role in dealing with COVID-19 pandemic problems. This study explored the hospital pharmacist's perception of their roles and behaviours and the influence factors during the COVID-19 pandemic period.Material and Methods: The research was conducted using phenomenological qualitative methods through in-depth online interviews using an online meetings platform. Informants were taken until the data was saturated. Credibility tests by member checking, dependability, and confirmability tests were performed to ensure data validity. The results of the interviews then were analyzed by thematic analysis.Results: Eight informants were included with 5 emerging themes revealed from this study. The theme consists of the pharmacist's high commitment to his important role as a team member of the healthcare provider in providing the best service by adapting their services, ensuring rational therapy for COVID-19 patients, and maintaining the availability of medicines, medical devices, and consumable medical materials. Furthermore, pharmacists described some innovation strategies, like drug delivery for outpatients and telepharmacy services. The supporting factors for pharmacists in their services were interprofessional collaboration between pharmacists and other healthcare providers. Support from colleagues, hospital management, government, donations and technology were also revealed as positive factors. The barrier factors included uncertain pandemic conditions, pharmacists who were exposed to the virus and the mental health condition of healthcare professionals during the pandemic.Conclusion: Pharmacists have a strong commitment to playing a crucial part in the healthcare team in offering the most treatment possible and providing management work. They created some innovative initiatives to tackle the COVID-19 burden. Supportive and barrier factors that affect pharmacist performance during pandemics were also disclosed and examined in this paper.Keywords: